Meningkatkan Ketahanan Pangan Provinsi Kalimantan Timur Melalui Haki Atas Varietas Tanaman Padi - Kuspraningrum, Emilda; Triyana, Lily; Noor Asufie, Khairunnisa; Hediati, Febri Noor (Jurnal Risalah Hukum, 2023)
Samarinda is the capital city of East Kalimantan Province which has an area 718.23 km² covering 10 Districts. East Kalimantan in general and Samarinda in particular are areas with tropical rain characteristics so they have soil types latosol who have low fertility rates. In order to meet the needs of the rice shortage, a thought is needed to create a generation of rice with a strong type and is suitable for planting on this infertile soil. It is necessary to involve the role of the government, local farmers and/or researchers to find and develop superior varieties of rice plants that are suitable for planting in the Samarinda region, this is intended to encourage the creation of new varieties of rice and protect the idea of ??creating new varieties of rice plants through intellectual property rights so that provide a better economic impact for all parties and maintain food security in the city of Samarinda. The research conducted is normative research, the discussion in this study leads to the utilization of plant variety protection so that it has a positive impact not only for plant breeders but also for the people of Samarinda city, as stated in Article 1 paragraph 4 of Law Number 29 of 2000 concerning varieties Plants, plant breeding is a series of research and testing activities or activities of discovery and development of a variety, in accordance with standard methods to produce new varieties and maintain the purity of the seeds of the varieties produced.